Factors Associated with the Non-Adherence of TB Screening in Children Aged - Lidwina Vania Shaynaputri; Anindita Soetadji; Dea Amarilisa Adespin; Stefani Candra Firmanti (Jurnal Kedokteran Diponegoro)
Background: TB screening in children having close contact with smear-positive TB patients is urgent to conduct to improve the case detection rate and to achieve the “End TB” target. In fact, the implementation of screening in Indonesia is still inadequate.